ТЕОРЕТИЧНІ ОСНОВИ ФІНАНСУВАННЯ ДОШКІЛЬНОЇ ОСВІТИ - Бучковська, Яна Георгіївна (Науковий журнал «Світ фінансів», 2017)
Бучковська Я. В. Теоретичні основи фінансування дошкільної освіти. Узагальнено позиції провідних вчених стосовно значення дошкільної освіти для соціального й економічного розвитку країни. Розвинуто теоретичні положення щодо фінансування послуг дошкільної освіти. Buchkovska Ja. Theoretical bases of financing of preschool education. The positions of leadinh scientists are generalized in relation to the walue of preschool education for social and economic development of country. Theoretical positions are developed in realision to financing of preschool education services.